Rhythmic subvocalization: An eye-tracking study on silent poetry reading - Judith Beck; Lars Konieczny (Journal of Eye Movement Research)
The present study investigates effects of conventionally metered and rhymed poetry on eye-movements in silent reading. Readers saw MRRL poems (i.e., metrically regular, rhymed language) in two layouts. In poem layout, verse endings coincided with line breaks. In prose layout verse endings could be mid-line. We also added metrical and rhyme anomalies. We hypothesized that silently reading MRRL results in building up auditive expectations that are based on a rhythmic “audible gestalt” and propose that rhythmicity is generated through subvocalization. Our results revealed that readers were sensitive to rhythmic-gestalt-anomalies but showed differential effects in poem and prose layouts. Metrical anomalies in particular resulted in robust reading disruptions across a variety of eye-movement measures in the poem layout and caused re-reading of the local context. Rhyme anomalies elicited stronger effects in prose layout and resulted in systematic re-reading of pre-rhymes. The presence or absence of rhythmic-gestalt-anomalies, as well as the layout manipulation, also affected reading in general. Effects of syllable number indicated a high degree of subvocalization. The overall pattern of results suggests that eye-movements reflect, and are closely aligned with, the rhythmic subvocalization of MRRL.